On tests for linearity against STAR models with deterministic trends - Hendrik Kaufmann; Robinson Kruse; Philipp Sibbertsen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
Linearity testing against smooth transition autoregressive (STAR) models when deterministic trends are potentially present in the data is considered in this paper. As opposed to recently reported results in Zhang (2012), we show that linearity tests against STAR models lead to useful results in this setting.
Keywords: C12; C22; 330; Nonlinearity; Smooth transition; Deterministic trend